Maize for the Gods unearthing the 9,000-year history of corn - Blake, Michael 1953- (University of California Press, 2015)
"Maize is the world's most productive food and industrial crop--grown in more than 160 countries and on every continent except Antarctica. Maize for the Gods brings together new research by archaeologists, archaeobotanists, plant geneticists, and a host of other specialists as they trace the history of Maize, exploring the complex ways that this single plant and the peoples who domesticated it came to be inextricably entangled with one another over the past nine millennia. From Maize's first appearance and domestication in ancient campsites and settlements in Mexico to its intercontinental journey throughout most of North and South America, this history is also the story of the artistic creativity, technological prowess, and social, political, and economic resilience of America's first peoples."--Provided by publisher